THE CHANGES IN FINANCIAL PERFORMANCE SEGMENTATION USING FINANCIAL RATIOS PHARMACEUTICAL COMPANIES IN INDONESIA - Nuria Soviatun; Jerry Heikal (Cerdika: Jurnal Ilmiah Indonesia, 2023)
The purpose of this study is to analyze the financial condition of pharmaceutical companies in Indonesia listed on the IDX. This study measures the ratios, namely net profit margin, debt to equity ratio, and return on equity based on financial reports as of June 2022 and June 2023. Data processing in this study used IBM SPSS software with K-means clustering analysis.From the clustering results, there were 5 clusters with 5 personas, namely Very Good (A), Good (B), Fair (C), Bad (D), and Very Bad. Persona grouping based on the ratio of NPM, ROE, and DER. There has been a change in financial performance segmentation from 2022 to 2023, where most of the pharmaceutical companies in Indonesia have experienced a decline in performance in 2023.From the results of the comparison above, it can be concluded that PT Pyridam Farma Tbk shows the most significant change in financial performance segmentation, from poor performance (D) in 2022 to very good (A) performance in 2023. Meanwhile, the financial performance of PT Indofarma Tbk from 2022 and 2023 has not experienced a change in segmentation, remains in a very bad position (E). The authors conclude that PT Pyridam Farma Tbk has the potential to become a company that will acquire PT Indofarma Tbk.